Piloting Augmented Reality Technology to Enhance Realism in Clinical Simulation. Issue 9 (September 2016) - Vaughn, Jacqueline; Lister, Michael; Shaw, Ryan J.
Abstract : We describe a pilot study that incorporated an innovative hybrid simulation designed to increase the perception of realism in a high-fidelity simulation. Prelicensure students (N = 12) cared for a manikin in a simulation lab scenario wearing Google Glass, a wearable head device that projected video into the students' field of vision. Students reported that the simulation gave them confidence that they were developing skills and knowledge to perform necessary tasks in a clinical setting and that they met the learning objectives of the simulation. The video combined visual images and cues seen in a real patient and created a sense of realism the manikin alone could not provide.